2006
DOI: 10.1128/jvi.00141-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 V1-V2 Envelope Loop Sequences Expand and Add Glycosylation Sites over the Course of Infection, and These Modifications Affect Antibody Neutralization Sensitivity

Abstract: Over the course of infection, human immunodeficiency virus type 1 (HIV-1) continuously adapts to evade the evolving host neutralizing antibody responses. Changes in the envelope variable loop sequences, particularly the extent of glycosylation, have been implicated in antibody escape. To document modifications that potentially influence antibody susceptibility, we compared envelope variable loops 1 and 2 (V1-V2) from multiple sequences isolated at the primary phase of infection to those isolated around 2 to 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
288
6
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(330 citation statements)
references
References 48 publications
(44 reference statements)
34
288
6
2
Order By: Relevance
“…It has a highly conserved length among early or transmitted/founder isolates and length and glycosylation of the V2 loop are commonly associated with escape from neutralizing antibodies. 30,35,65 Furthermore, V2 contains a putative a 4 b 7 integrin-binding motif of uncertain significance. 39 Although 1454 KARASAVVAS ET AL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has a highly conserved length among early or transmitted/founder isolates and length and glycosylation of the V2 loop are commonly associated with escape from neutralizing antibodies. 30,35,65 Furthermore, V2 contains a putative a 4 b 7 integrin-binding motif of uncertain significance. 39 Although 1454 KARASAVVAS ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Sequence variation within the V1/V2 loops alters neutralization resistance and viral escape is associated with V2 loop mutations. [29][30][31][32][33] Compared to viruses circulating in chronically infected persons, transmitted viruses (subtypes A and C) appear to have shorter V1/V2 regions and fewer N-linked glycosylation sites. 30,[34][35][36] The V2 loop contains a putative a 4 b 7 integrin binding motif (LDI/V) at amino acid (aa) residues 179-181 (HBX2 numbering system) that was shown to interact with the gut mucosal homing receptor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the course of this study, we found that KNH1144 SOSIP gp140 trimers from which the MPER was deleted (SOSIP.664) adopt a monodisperse distribution in the absence of detergent. 5 This property makes them more suitable than SOSIP.681 trimers for BN-PAGE, biophysical analyses, and EM studies. We confirmed that Endo H removed similar amounts of glycans from KNH1144 SOSIP.664 and SOSIP.681 trimers, as judged by SDS-PAGE analysis (not shown).…”
Section: Deglycosylation Strategy For Recombinant Env-mentioning
confidence: 99%